Estudos sobre imaginação e criação: contribuições de Lev Semenovich Vigotski e Cornelius Castoriadis - Furtado, Vanessa Clementino (2013)
This Master's Degree dissertation proposed to analyze the concepts of Imagination and Creation in the theories of Vygotsky and Castoriadis, Both the authors are proximate in their discussion on the specifically human activity based on the use of imagination and creativity; when they relate to the possibility of äcting in freedom". This activity permits us to adapt and/or transform hature, to the point of transcending biological laws and the very phusis. Thus, this investigation extended on the relation between Imagination and Creation relative to human liberty, in an attempt to offer subsidies to psicosocial praxis. However, research proposing to study activities marked by metaphysics, has for its guiding light the interrogation on the preponderance of reason. theoretical research was done on an extensive analysis of the works of both authors, with a selection of texts where these themes were dealt with and correlated witht he principal concepts and epistemological and ontological pressupositions sustaining each theory. A search was also made in the Capes databank with the following keywords: Vigotski [and variations of this spelling], Castoriadis,Imagination and Creation. Vygotsky, based on marxism, attempts to comprehend the psychological and social indissociable modes, attempting to found the formation of a "socialist man", who, in his essence must be freee, despite social determinations. cstoriadis founds a new ontology based on the "imaginary element", where h goes on to criticize the prevalence of reason, prisioned with determinity. In this way, both the authors offer us, despite their epistemological and ontological differences, a refernce for comprehending the acts of human beings in their completude. Reason, emotion, Creation and Imagination and, thus, the possibility of libert